Expansion of the investor base for the energy transition. (June 2019) - McInerney, Celine; Bunn, Derek W.
Abstract: Despite the emergence of the green bond market, the Energy Service Company (ESCO) model and green investment banks, the opportunities which the world's capital markets present to increase the pool of potential investors and reduce project financing costs for renewable, energy efficient and low carbon assets remain under-exploited. This has been a persistent concern for policy-makers. We review the appeal of this sector to different classes of investor and assess the successes and failures of several innovative products including securitisations, yieldcos, green bonds, green investment banks and crowdfunding. We analyse the experiences with these products and suggest that policy needs to recognise how fiscal initiatives can leverage their inherent appeal. Highlights: Significant finance is required for low carbon transition. Opportunity for global equity and debt capital markets to provide capital has not been exploited. Innovative financing mechanisms are required to attract capital market funds. Paper critiques innovative finance products and suggests policy interventions to leverage these.